¿Qué hacemos las enfermeras? Profesionalización, autonomía y asociatividad de la enfermería chilena, 1940-1960 - María Soledad Zárate (Centre de Recherches sur les Mondes Américains, 2019)
Chilean nursing experienced important processes of professional autonomy and construction of a public voice between 1940 and 1960, supported by a series of scientific and professional meetings, both national and international, sponsored by the Rockefeller Foundation and the Pan American Health Office, among others international organizations. Likewise, the National Health Service, founded in 1952, strengthened the definition of functions and the leadership of these professionals from its early years, by virtue of the importance of the benefits they fulfilled. Privileging the analysis of primary sources produced by the nurses themselves, and their reflections on their work, this article describes some of these processes, shedding light on the history of this profession, and its decisive contribution to the implementation of health policies in Chile. mid 20th century.